2015
DOI: 10.14689/ejer.2015.61.4
|View full text |Cite
|
Sign up to set email alerts
|

Learning Environments Designed According to Learning Styles and Its Effects on Mathematics Achievement

Abstract: Problem Statement: While designing a learning environment it is vital to think about learner characteristics (learning styles, approaches, motivation, interests… etc.) in order to promote effective learning. The learning environment and learning process should be designed not to enable students to learn in the same manner and at the same level, but rather designed by giving thought to students' existing learning styles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 16 publications
3
35
0
2
Order By: Relevance
“…An individual's learning style not only shows how he learns but also provides information about how to design a learning environment [15]. In relation to this matter there are four models of learning styles Kolb.…”
Section: E Learning Style Learningmentioning
confidence: 99%
“…An individual's learning style not only shows how he learns but also provides information about how to design a learning environment [15]. In relation to this matter there are four models of learning styles Kolb.…”
Section: E Learning Style Learningmentioning
confidence: 99%
“…One study by (Alias, 2014) that evaluated students' performance based on active learning style has shown the usefulness learning based on the learning preferences of a learner. Learning style index is a system designed to promote effective learning (Ozerem, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These experiences can be acquired by interacting with the learning environment (Bolliger, 2004). Studies have shown that learning environments that consider learner characteristics affect academic success in a positive way (Ozerem & Akkoyunlu, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%